2020
DOI: 10.1016/j.ultrasmedbio.2019.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Shear Wave Elastography in the Evaluation of Temporomandibular Joint Disorders

Abstract: We aimed at verifying the usefulness of shear wave elastography in determining the temporomandibular disc stiffness in patients with a temporomandibular disorders (TMDs). The study included 37 patients with confirmed TMDs and 208 healthy volunteers. Patients presented with significantly greater stiffness of the intermediate zone of the disc (region of interest [ROI] 1) and significantly lower stiffness of its anteriorly displaced portion (ROI 3). A receiver operating characteristics analysis indicated that a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Later, in 2013 Fatih Kantarci [ 17 ] suggested that SWE can be utilized in the diagnosis of temporomandibular disorders(TMD)since it was highly reproducible in the assessment of median nerve hardness. This conclusion was subsequently again verified by another study in 2019 which demonstrated a decrease in anterior malleolar disc stiffness of less than 8.667 kPa could accurately identify patients with TMD [ 18 ]. During the same period, Gürün E [ 19 ] proposed that the use of SWE examination to find brachial plexus nerve roots in patients with Multiple sclerosis has an increase in elasticity values and a decrease in diameter values, and his findings are consistent with the demyelinating process of the peripheral nervous system due to Multiple sclerosis.In 2016, Atilla Suleyman Dikici et al [ 20 ] first proposed the application of SWE to the detection of DPN and they found that increased stiffness of the tibial nerve in the lower limbs could be a surrogate for the diagnosis of DPN with high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 66%
“…Later, in 2013 Fatih Kantarci [ 17 ] suggested that SWE can be utilized in the diagnosis of temporomandibular disorders(TMD)since it was highly reproducible in the assessment of median nerve hardness. This conclusion was subsequently again verified by another study in 2019 which demonstrated a decrease in anterior malleolar disc stiffness of less than 8.667 kPa could accurately identify patients with TMD [ 18 ]. During the same period, Gürün E [ 19 ] proposed that the use of SWE examination to find brachial plexus nerve roots in patients with Multiple sclerosis has an increase in elasticity values and a decrease in diameter values, and his findings are consistent with the demyelinating process of the peripheral nervous system due to Multiple sclerosis.In 2016, Atilla Suleyman Dikici et al [ 20 ] first proposed the application of SWE to the detection of DPN and they found that increased stiffness of the tibial nerve in the lower limbs could be a surrogate for the diagnosis of DPN with high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 66%